Adverse childhood experiences and autonomic regulation in response to acute stress: the role of the sympathetic and parasympathetic nervous systems. Issue 2 (4th March 2017) - Winzeler, Katja; Voellmin, Annette; Hug, Evelin; Kirmse, Ursula; Helmig, Simone; Princip, Mary; Cajochen, Christian; Bader, Klaus; Wilhelm, Frank H.
ABSTRACT: Background and objectives : After a previous report demonstrated blunted heart rate (HR) reactivity in association with adverse childhood experiences (ACEs) [Voellmin, A., Winzeler, K., Hug, E., Wilhelm, F. H., Schaefer, V., Gaab, J., … Bader, K. (2015). Blunted endocrine and cardiovascular reactivity in young healthy women reporting a history of childhood adversity. Psychoneuroendocrinology, 51, 58–67. doi:10.1016/j.psyneuen.2014.09.008 ], the present analysis aimed at clarifying the role of the sympathetic and parasympathetic branches of the autonomic nervous system in this relationship. Design and Methods : One hundred eighteen healthy young women provided data on ACEs and underwent psychosocial stress testing. Systolic blood pressure (SBP) and respiratory sinus arrhythmia (RSA, quantified by high-frequency HR variability) were assessed as measures of sympathetic and parasympathetic cardiovascular activity, respectively. A mediation model was calculated to test the indirect effects of ACEs on HR via SBP and RSA. Results : The effect of ACEs on HR reactivity was mediated by SBP reactivity but not by RSA reactivity. ACEs were associated with reduced SBP at rest. Conclusions : ACEs were associated with down-regulation in a measure of sympathetic but no alteration in a measure of parasympathetic cardiovascular stress reactivity in adulthood. Future research will need to clarify whether this indicates risk or resilience.